Sweetness preference and its impact on energy intake and body weight – a review of evidence - Prinz, Philip (Frontiers in Nutrition, 2023)
In the last few years, several approaches have been postulated for tackling the global increase in overweight and obesity rates, including different dietary macronutrient compositions or the timing of meals. Recently, taste modulation has come into focus as a possible approach for influencing dietary behavior. The perception of sweet taste is innate and an evolutionary protection mechanism to prevent primates from eating poisonous plants. It is hypothesized that this innate sweetness preference could be modulated by dietary sweetness, including sweet foods and beverages, which results in a learned sweetness preference that affects energy intake and body weight. However, this hypothesis is not supported by unanimous scientific evidence. This review provides an update of the current literature, regarding the modulation of sweetness preference as a possible new approach in the prevention of overweight and obesity. In general, results from observation as well as interventional studies in all age groups are heterogeneous. The majority showed no effect of dietary sweetness modulation on sweetness preference, energy intake or anthropometric measures. Therefore, the modulation of sweetness preference due to diet, foods or beverages is still a hypothesis and not scientifically proven. However, due to the lack of data, more research is necessary.